Studies on the Nitrogen-Fixing Bacteria of the Genus Azotobacter in Libyan Soils - BADAWY, FARIDA H. (The Libyan Journal of Agriculture, 2023)
The numbers of Azotobacter in some Libyan soils, determined by the most probable number technique, varied from few cells (less than 10) to as many as 30 thousands per gram of soil. The abundance was favourably affected by cultivation of the soil and the amount of organic materials, and deterimentally affected by the high salt concentration in soil. Studies on the morphological, cultural and nutritional characteristics of 12 isolates revealed that one isolate resembled A. vinelandii (Lipman) and the rest of the isolates resembled A. chroococcum (Beijerinck). The differential use of the pentoses: xylose, arabinose and ribose by A. vinelandii and not by A. chroococcum was used as a taxonomic criterion for differentiating between these two species.